Análise da produtividade marginal dos recursos agrícolas, no município de Varginha, Minas Gerais - Zeballos H, Hernán; R Teixeira Filho , Antônio; T Pond, Martin (Revista Ceres, 2025)
The present work attempts to identify the actual use of agricultural resources in the county of Varginha, in the southern region of the state of Minas Gerais and analize how efficiently these resources are being used.